The complete mitochondrial genome of leafhopper Atkinsoniella nigrita (Hemiptera: Cicadellidae) with the shortest 12S rRNA and longest tRNA-Lys of the Atkinsoniella genus - Hu Li; Kai Yu; Rui Zhao; Gang Wu; Chuan-Feng Xiong (Mitochondrial DNA. Part B. Resources, 2023)
The complete mitochondrial genome (mitogenome) of the leafhopper Atkinsoniella nigrita Zhang & Kuoh, was determined in this study. The entire sequence was 16,011 base pairs (bp) in length. The new mitogenome consists of a typical set of genes: 13 protein-coding genes (PCGs), two ribosomal RNA (rRNA) genes, 22 transfer RNA (tRNA) genes, and one control region of 1720 bp in length. The base composition of the mitogenome was A = 41.7%, T = 38.2%, C = 10.7%, and G = 9.4%. This is the classical structure for most insect mitogenomes without any gene arrangement observed. Compared with other known mitochondrial genomes of 15 Atkinsoniella species, the new mitogenome with three PCGs (ND2, ND5, and ND4L) shared the same gene base length, start codon and stop codon, and the shortest 12S rRNA (729 bp) and the longest tRNA-Lys (73 bp) within the genus Atkinsoniella. A phylogenetic analysis of 31 Cicadellinae and two Ledrinae concatenated sequences of 13 PCGs of their mitogenomes using Bayesian inference (BI) revealed that A. nigrita belongs to the genus Atkinsoniella with strong nodal support (BI posterior probability = 1).